Association between Hair Hygiene and Pediculus capitis Infestation among Elementary School Students in Sukorambi District, Jember Regency - Ali, Alya Maulidya; Nurdian, Yudha; Rumastika, Nindya Shinta (Indonesian Journal of Tropical and Infectious Disease, 2025)
Pediculus humanus capitis (P.h. capitis) is an ectoparasite which inhabits hair and scalp of human, causing a neglected disease called Pediculus humanus capitis infestation or pediculosis capitis. This disease, easily transmitted between people directly or indirect, often affects girls around 3–12 years old in tropical countries with high humidity. This can be avoided with applying personal hygiene focused on hair area (hair hygiene). Hair hygiene in this study was divided into several parameters, such as frequency of hair washing, shampoo usage, hair drying, towel sharing habit, comb and hair accessories sharing habit, head cover sharing habit, and close contact with an infested person. The aim of this study is not only to know the prevalence of P. h. capitis infestation, but also to determine the correlation between hair hygiene and P. h. capitis infestation among elementary school students in Sukorambi District, Jember Regency. This study was held around January to February 2024 using cross-sectional approach with total 83 respondents. Respondents were given several questions about parameters of hair hygiene and their hair was examined using lice comb to find P. h. capitis. Prevalence of Pediculosis capitis infestation among elementary school students in Sukorambi District reached 71.1%. Statistical analysis showed that towel sharing habit and comb and other hair accessories sharing habit had a significant relationship with P. h. capitis infestation (p-value <0.05). Multivariate analysis using logistic regression showed that comb and other hair accessories sharing habit were the most significant hair hygiene parameters.